«On seven dashing blowing winds...» (About book by D. I. Petin «The History of the Omsk clan of Batyushkin») - A. A. Shtyrbul (Омский научный вестник: Серия "Общество. История. Современность")
The paper analyzes the monograph «The History of the Omsk clan of Batyushkin» prepared by the Omsk historian-archivist and public figure, candidate of historical sciences, associate professor D. I. Petin. The author analyzes the peculiarities of the author’s approach to coverage on the example of a single Omsk family and the mansion of political and social history that belonged to it in more than a century of the functioning of the Russian statehood. The scientific, methodological novelty of the monograph is noted; as critical passages, certain aspects are highlighted, with which the author of the review does not fully agree. In the final, a conclusion is made about the high significance of the analyzed book novelty.